PENGARUH PENGARUH PENGGUNAAN MEDIA POWERPOINT DAN INTESITAS BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMAN 1 RANAH PESISIR - Winda Mawarni; Caterina Lo; Irman (Ekasakti Educational Scientific Journal, 2025)
This research aims to analyze 1) whether there is an influence of the use of Powerpoint media on student learning outcomes in Class X Economics Subjectsat SMAN I Pesisir Region. 2) Is there an influence of learning intensity on student learning outcomes in economic ssubjects for class X SMAN I Coastal Region. 3) Is there an influence of the use of Powerpoint media and learning intensity on student learning outcoes in class X economic ssubjects at SMAN I Ranah  Pesisir. This  type of research is  kuantitatif  research. The population in this study was 297 students. Purposive sampling, the sample obtained was 63 students. The instrument used for research is a questionnaire using the Multiple Linear Regression test and hypothesis testing usingthe t testand F test. The research resultss how that: 1) Thereis a positive and significant influence between the use of Powerpoint media (X1) on student learning outcomes in Class X Economics Subjectsat SMAN I Ranah Pesisir.